Final Year Student’s Perception before Engaging Engineering Technology Program in UTeM - Harun, Mohamad Haniff; Al-Amani, Umar; Nor Hamizah, Miswan; Hamzah, Khairum; Ahmad Zubir , Jamil; Abdullah, Rohana; Yusoff, Mohd Rahimi (2016)
In line with industrial development which is growing rapidly in Malaysia, the country is in great needs of competent technical workforce able to apply the latest concept of technology, improve equipment and system utilization, optimizing operation and maintenance of equipment. Therefore, an engineering technology program will be introduced in Malaysia education system at higher level. In determining the perception of Engineering Technology program in Universiti Teknikal Malaysia Melaka (UTeM), a market survey has been conducted to gather the perception of the final year students about Engineering Technology. Total numbers of 123 students from Cohort 1 with two different departments, electrical and manufacturing were used as a sample space. The scope of the market survey covered regarding their perspective and understanding of Engineering Technology before enrolling engineering technology program from their perspective courses. The findings show that there is a difference perception in overall especially regarding their understanding of terms Engineering Technology Programs.